Experimental study on ferritic stainless steel RHS and SHS beam-columns. (March 2016) - Arrayago, I.; Real, E.; Mirambell, E.
Abstract: Ferritic stainless steels, with their lower nickel content, supplement the desirable features offered by different stainless steel grades with a more controlled and lower initial investment requirements, which have encouraged the use of these materials in construction. The nonlinear behaviour of stainless steel grades is not usually considered when extending design expressions codified for carbon steel to these alloyed materials, leading to overconservative design approaches and the applicability of the different design expressions initially developed for carbon steel needs to be adjusted for every stainless steel grade. The study of stainless steel elements subjected to combined flexural buckling and bending moment loading conditions only covers the most usual austenitic, duplex and lean duplex grades, but experimental results on ferritic grades are still necessary to complete the analysis. Hence, an experimental programme on ferritic stainless steel RHS and SHS pin-ended elements has been conducted where the flexural buckling and beam-column behaviour of these elements has been investigated. Furthermore, the assessment of the different design approaches for flexural buckling and interaction expressions for combined loading has been derived from the obtained experimental results, and current specifications provided in Standards have been found to be, in general, safe but overconservative. Highlights: Experimental programme on ferritic stainless steel RHS and SHS elements is presented. Flexural buckling resistance of pin-ended columns is investigated. Design expressions for flexural buckling resistance predictions are assessed. Beam-column behaviour of pin-ended columns under uniform bending is studied. Codified and alternative interaction expressions for beam-columns are assessed.